The Effects of Earthworms on Fungal Diversity and Community Structure in Farmland Soil With Returned Straw - Song, Ke; Sun, Yafei; Qin, Qin; Sun, Lijuan; Zheng, Xianqing; Terzaghi, William; Lv, Weiguang; Xue, Yong (Frontiers in Microbiology, 2020)
Background To promote the decomposition of returned straw, reduce the incidence of soil-borne diseases caused by returned straw, and accelerate the conversion of straw carbon into soil carbon, we inoculated earthworms into fields with returned straw. The earthworms accelerated straw degradation and promoted carbon conversion. However, the impact of externally inoculated earthworms on the farmland soil ecosystem, especially the structure and the function of its microbial community, remains unclear. Methods We analyzed the effects of straw return and earthworms on the diversity of fungal populations and the community structure of dominant fungal taxa in soil by quantifying fungal population size and community composition via PCR amplification of internal transcribed spacer genes and 18S rRNA gene sequencing. Results The results showed that earthworm inoculation significantly accelerated the degradation of rice straw and promoted the conversion of straw carbon to soil carbon. Both fungal abundance and α-diversity (Sobs and Shannon indices) were higher in the plots with surface straw but without earthworms than in those inoculated with earthworms and in the CK. Principal component analysis indicated that straw return increased the diversity and the abundance of the fungal community, whereas earthworms inhibited this expansion of the fungal community caused by straw return. Interestingly, the overall differences in fungal community composition were smallest in plots with straw return, while the dominant fungal community features in plots inoculated with earthworms were closer to those of the CK. Conclusion Generally, straw return stimulated unclassified_K_fungi, Pseudeurotium, and Fusarium with strong cellulolytic ability. In contrast, the abundances of Stachybotrys, unclassified_c_Sordariomycetes, unclassified_f_Lasiosphaeriaceae, and Schizothecium were higher in the plots inoculated with earthworms and in the CK. Furthermore, evolutionary analysis showed that the evolution of soil fungal communities tended to diverge after straw return, and the evolutionary directions of fungal species in the plots inoculated with earthworms were similar to those in the CK.